New Nutraceutical Combination Reduces Blood Pressure and Improves Exercise Capacity in Hypertensive Patients Via a Nitric Oxide–Dependent Mechanism. Issue 5 (3rd March 2020) - Carrizzo, Albino; Moltedo, Ornella; Damato, Antonio; Martinello, Katiuscia; Di Pietro, Paola; Oliveti, Marco; Acernese, Fausto; Giugliano, Giuseppe; Izzo, Raffaele; Sommella, Eduardo; Migliarino, Serena; Piazza, Ornella; et al.
Abstract : Background: High blood pressure (BP) has long been recognized as a major health threat and, particularly, a major risk factor for stroke, cardiovascular disease, and end‐organ damage. However, the identification of a novel, alternative, integrative approach for the control of BP and cardiovascular protection is still needed. Methods and Results: Sixty‐nine uncontrolled hypertension patients, aged 40 to 68 years, on antihypertensive medication were enrolled in 2 double‐blind studies. Forty‐five were randomized to placebo or a new nutraceutical combination named AkP05, and BP, endothelial function, and circulating nitric oxide were assessed before and at the end of 4 weeks of treatment. Twenty‐four patients were randomized to diuretic or AkP05 for 4 weeks and underwent a cardiopulmonary exercise test to evaluate the effects of AkP05 on functional capacity of the cardiovascular, pulmonary, and muscular systems. Vascular and molecular studies were undertaken on mice to characterize the action of the single compounds contained in the AkP05 nutraceutical combination. AkP05 supplementation reduced BP, improved endothelial function, and increased nitric oxide release; cardiopulmonary exercise test revealed that AkP05 increased maximum O2 uptake, stress tolerance, and maximal power output. In mice, AkP05 reduced BP and improved endothelial function, evoking increased nitric oxide release through the PKCα/Akt/endothelial nitric oxide synthase pathway and reducing reactive oxygen species production via NADPH‐oxidase inhibition. These effects were mediated by synergism of the single compounds of AkP05. Conclusions: This is the first study reporting positive effects of a nutraceutical combination on the vasculature and exercise tolerance in treated hypertensive patients. Our findings suggest that AkP05 may be used as an adjunct for the improvement of cardiovascular protection and to better control BP in uncontrolled hypertension.